IMPLEMENTASI JUST IN TIME TERHADAP EFISIENSI PASOKAN BAHAN LEATHER DI PABRIK GLOVE PT ADI SATRIA ABADI - Syahrul Hidayatullah; Widya Setiafindari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Poorly managed raw material inventory can lead to cost inefficiencies, stock accumulation, and disruptions in production flow. PT Adi Satria Abadi, a glove manufacturing company, has experienced excessive leather raw material inventory due to a procurement system that has not yet been optimally implemented. This study aims to analyze the application of the Just-In-Time (JIT) method in improving the efficiency of leather raw material supply and reducing inventory costs. The research employs a quantitative descriptive method with a case study approach, using data on raw material purchases, material usage, inventory costs, and ordering frequency. The analysis compares conditions before and after the implementation of the JIT method, including optimal order quantity, total inventory cost, and storage efficiency. The results show that the implementation of the JIT method reduced inventory costs by 59.2%, decreased idle stock by 37%, and improved the smoothness of raw material supply by 36.36%. Therefore, the JIT method can serve as an effective solution for companies in managing leather raw material inventory efficiently and sustainably.